Ważniejsze czynniki stymulujące i ograniczające rozwój logistyki organizacji sieciowych - Gołembska, Elżbieta (Important Factors of Logistics Development in Network Organizations, 2005)
The aim of presentation is to show the most important stimulationing and destimulations factors in term of developing logistics network.This presentation consider also third - stage cooperation model in the network and fuzzy logic model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 57-65